IMPLEMENTASI PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Mayang Chris Mahajeng; Ahmad Fauzi Hendratmoko (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The advancement of 21st century technology has a substantial influence on various aspects of life, critical thinking skills are one of the important skills that students must have in the advancement of 21st century technology. The purpose of this study is to describe students' critical thinking skills. This type of research uses a pre-experimental design using a one-group pretest-posttest design. The research sample was 27 students of class VII-B of SMP Labschool UNESA 1 Surabaya, sampling using purposive sampling. The instruments used in this study were pretest and posttest sheets, with data collection techniques through tests. The improvement of students' critical thinking skills obtained a normality value of 0.097 then a Paired t-Test was conducted with a significance value of <0.001 meaning that there was a difference between the pretest and posttest scores in the implementation of PBL to improve students' critical thinking skills. The improvement of students' critical thinking skills was also analyzed using N-gain which obtained a medium to high category on each indicator used and, analyzed using an effect size which was in the high category with a value of 5.63. Thus, based on these results, it can be concluded that implementing the PBL model can improve students' critical thinking skills.